Pengembangan Model Pembelajaran Rissca Dalam Perkuliahan Kajian Kurikulum Bahasa dan Sastra Indonesia - Rina Rosdiana; Siti Chodijah; Ainiyah Ekowati (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The research is aimed at designing a learning process that can stimulate the activity of students’ analytical thinking on the subject of the Curriculum of Indonesian Language and Literatures. The method used is research and development with 4D version. The result of the research is a learning model which is lesson study based focused on developing the concept of cooperative and scientific method, namely RISSCA (Reading, Identifying, Sequencing, Sharing, Communicating, Assessing). In this model, the materials chosen are systematically and procedurally arranged. On the subject of the Curriculum of Indonesian Language and Literatures, the materials that are suitable with this model are the understanding of the development of curriculum naming, core and basic competencies, the development of learning approach, syllabus compiling, the introduction of lesson planning, learning assessment of KTSP and the curriculum of 2013. The learning result achieved by implementing RISSCA is very good. The average score of each cycle reaches 72; 82,4; 84,3; and 87.